2016
DOI: 10.1093/infdis/jiw157
|View full text |Cite
|
Sign up to set email alerts
|

Interferon α–Enhanced Clearance of Group A Streptococcus Despite Neutropenia

Abstract: These findings help to explain the rather discrepant facts of neutropenia but preserved antibacterial immune defenses in patients treated with IFN-α.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…Conversely, the human but not mouse TLR8 appears to be involved in type I IFN induction by bacterial RNA (59). Some antimicrobial functions of human neutrophils are enhanced by type I IFNs (78) whereas such stimulatory effects have so far not been described in mouse neutrophils. Future work should put more emphasis on studies of common and distinct features of type I IFN functions in bacterial infections.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the human but not mouse TLR8 appears to be involved in type I IFN induction by bacterial RNA (59). Some antimicrobial functions of human neutrophils are enhanced by type I IFNs (78) whereas such stimulatory effects have so far not been described in mouse neutrophils. Future work should put more emphasis on studies of common and distinct features of type I IFN functions in bacterial infections.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in vivo studies in mice indicate that S. aureus -triggered type I IFNs can be detrimental ( 45 ). On the other hand, type I IFN signaling is required to control disease and increase survival rate after other pathogenic bacterial infections, including Group A streptococci ( 46 ), Group B streptococci, pneumococci, E. coli ( 47 ), and Streptococcus pyogenes ( 48 ). In cattle, a single study reported that S. uberis could upregulate the transcription of IFN-ω ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, P levels did not appear to drop further in persons with more prolonged neutropenia, suggesting that cells other than neutrophils contribute significantly to P synthesis. Indeed, T cells and monocytes/macrophages also synthesize P [9–11, 20] and could contribute to the pool of circulating P in the absence of neutrophils. An alternative explanation is that the half-life for P is long.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the effects of lower P levels and the resulting decrease in C3 convertase stability are likely to be manifest at lower serum concentrations. Uchiyama et al [20] recently reported that individuals receiving interferon (IFN)-α treatment for hepatitis C had increased P levels compared with pre- or posttreatment levels. They demonstrated that treating monocytes and neutrophils with IFN-α resulted in increased P release from these cells in culture.…”
Section: Discussionmentioning
confidence: 99%